2013
DOI: 10.1073/pnas.1321167110
|View full text |Cite
|
Sign up to set email alerts
|

Emerging predictable features of replicated biological invasion fronts

Abstract: Biological dispersal shapes species' distribution and affects their coexistence. The spread of organisms governs the dynamics of invasive species, the spread of pathogens, and the shifts in species ranges due to climate or environmental change. Despite its relevance for fundamental ecological processes, however, replicated experimentation on biological dispersal is lacking, and current assessments point at inherent limitations to predictability, even in the simplest ecological settings. In contrast, we show, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
121
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(125 citation statements)
references
References 52 publications
3
121
0
1
Order By: Relevance
“…The linear landscapes (Fig. 1) used in the experiments were channels drilled on a Plexiglas sheet (61). A second Plexiglas sheet was used as a cover, and a gasket prevented water spillage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The linear landscapes (Fig. 1) used in the experiments were channels drilled on a Plexiglas sheet (61). A second Plexiglas sheet was used as a cover, and a gasket prevented water spillage.…”
Section: Methodsmentioning
confidence: 99%
“…Density estimates were obtained by placing the linear landscape under the objective of a stereomicroscope (Olympus SZX16), taking pictures (with the camera Olympus DC72), and counting individuals through image analysis as in ref. 61. Stationary density profiles were measured after 210 min from the introduction of cells in the landscape.…”
Section: Methodsmentioning
confidence: 99%
“…Melbourne and Hastings (31) have carried out a very detailed comparison between theory and experiment for a laboratory population of flour beetles and showed that the unavoidable heterogeneity of the founding organisms leads to large variation in the rate of spread between replica populations. At the microscopic scale, Wakita et al (32) tested the expected relation between the rate of spread and nutrient availability in Escherichia coli, and Giometto et al (33) used the theory of pulled waves to describe the expansion of tetrahymena in linear channels. All of these studies, however, focused only on the rate of invasion and did not test theoretical predictions for the shape of the invading fronts.…”
Section: Significancementioning
confidence: 99%
“…However, such experiments can guide our thinking, show which theoretical predictions may be observable in nature (34,35), and help develop new models (36). For example, range expansions of microbial populations have revealed the dependence of the invasion velocity on the supply of resources (37) and demographic stochasticity (33). Experiments with microbes have also demonstrated the strong effect of range expansion on competition (38)(39)(40)(41)(42)(43)(44) and neutral evolution via the founder effect or gene surfing (45,46).…”
Section: Significancementioning
confidence: 99%
“…Several studies show, however, that 2D tracking successfully predicts spread rates even in higher dimensional systems (Giometto et al. 2014; Pennekamp 2014). Complex environments with many physical obstacles (e.g., debris particles in our medium) prevent reliable tracking in three dimensions, because individuals may be frequently invisible to one of the three required cameras.…”
Section: Discussionmentioning
confidence: 99%